Penerapan Algoritma Batchelor-Wilkins dalam Pengklasteran Graf - Christyan Tamaro Nadeak (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2023)
Batchelor-Wilkins Algorithm is a simple and heuristic clustering algorithm used when the number of classes is unknown. In this paper we will use Batchelor-Wilkins algorithm in graph clustering, specifically a Banana Tree Graph B(n,k), a graph obtained by connecting one leaf of each of n copies of a complete bipartite graph K_1,k-1 to a single root vertex.